ELK1 Enhances Pancreatic Cancer Progression Via LGMN and Correlates with Poor Prognosis - Yan, Qiang; Ni, Chenming; Lin, Yingying; Sun, Xu; Shen, Zhenhua; Zhang, Minjie; Han, Shuwen; Shi, Jiemin; Mao, Jing; Yang, Zhe; Wang, Weilin (Frontiers in Molecular Biosciences, 2021)
Pancreatic cancer is one of the most lethal cancers and its prognosis is extremely poor. Clarification of molecular mechanisms and identification of prognostic biomarkers are urgently needed. Though we previously found that LGMN was involved in pancreatic carcinoma progression, the upstream regulation of LGMN remains unknown. We used reliable software to search for the potential transcription factors that may be related with LGMN transcription, we found that ELK1 could be a new regulator of LGMN transcription that binded directly to the LGMN promoter. Moreover, knocking down of ELK1 reduced pancreatic cancer cells proliferation, invasion and survival, while LGMN restored the malignancy of pancreatic cancer in vitro and in vivo. Overexpression of ELK1 further increased cancer cells proliferation, invasion and survival. Clinically, ELK1 and LGMN were positively correlated with clinical stage, degree of differentiation and Lymph node infiltration. ELK1 and LGMN were identified as independent prognostic factors for overall survival. The patients with low expression of ELK1/LGMN survived an average of 29.65 months, whereas those with high expression of ELK1/LGMN survived an average of 16.67 months. In conclusive, our results revealed a new mechanism by which ELK1 promoted the progression of pancreatic cancer via LGMN and conferred poor prognosis.